Mimetics of Hormetic Agents: Stress-Resistance Triggers - Joan Smith Sonneborn (SAGE Publishing, 2010)
Mimetics of hormetic agents offer a novel approach to adjust dose to minimize the risk of toxic response, and maximize the benefit of induction of at least partial physiological conditioning. Nature selected and preserved those organisms and triggers that promote tolerance to stress. The induced tolerance can serve to resist that challenge and can repair previous age, disease, and trauma damage as well to provide a more youthful response to other stresses. The associated physiological conditioning may include youthful restoration of DNA repair, resistance to oxidizing pollutants, protein structure and function repair, improved immunity, tissue remodeling, adjustments in central and peripheral nervous systems, and altered metabolism. By elucidating common pathways activated by hormetic agent's mimetics, new strategies for intervention in aging, disease, and trauma emerge. Intervention potential in cancer, diabetes, age-related diseases, infectious diseases, cardiovascular diseases, and Alzheimer's disease are possible. Some hormetic mimetics exist in pathways in primitive organisms and are active or latent in humans. Peptides, oligonucleotides, and hormones are among the mimetics that activate latent resistance to radiation, physical endurance, strength, and immunity to physiological condition tolerance to stress. Co-activators may be required for expression of the desired physiological conditioning health and rejuvenation benefits.